Future Plans of Iraqi Physicians in Jordan: Predictors of Migration. (18th March 2013) - Malik, Sana; Doocy, Shannon; Burnham, Gilbert
Abstract The continuing violence in Iraq has led to further damage to the health sector in a country already affected by sanctions, war and harsh rule. As a consequence some doctors have been killed and others have migrated, both within Iraq and from Iraq to neighbouring countries. In this article we report patterns of migration of Iraqi physicians, identify perceived future plans, and assess factors behind physicians' decisions. Respondent driven sampling in 2007 was used to interview 401 Iraqi medical doctors who migrated to Jordan after the 2003 invasion of Iraq The main outcome measure for this study was the future plans of physicians, which included permanently residing outside Iraq or returning to Iraq. Physicians who planned to return to Iraq differed from those who planned to reside permanently outside Iraq in the following factors: age categories (relative odds comparing age 50 plus to those under 30 = 0.46, 95% CI: 0.21–0.97), years spent outside of Iraq (RO = 2.03, 95% CI = 1.28–3.21), no difficulties in Jordan (RO = 0.53, 95% CI = 0.31–0.93), and household members residing in Iraq (RO = 1.17, 95% CI = 1.05 – 1.31). Many doctors who fled Iraq after the 2003 invasion do not plan to return, which must be considered in future training strategies for the Iraqi health sector.